2012
DOI: 10.1200/jco.2012.42.0240
|View full text |Cite
|
Sign up to set email alerts
|

Improving Survival Trends in Primary Myelofibrosis: An International Study

Abstract: Survival of PMF is steadily improving, except in patients in poor-risk categories. This observation must be taken into account at the time of evaluating the survival impact of newer therapies for PMF, which are currently being tested in these patient subpopulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 31 publications
5
89
0
2
Order By: Relevance
“…An International Working Group project reviewing the outcome of patients with intermediate-2 or high-risk myelofibrosis over the last several decades, also found that outcome of patients had not changed over time. 23 Mindful of the caveats associated with historical comparisons, we observed an overall survival benefit for ruxolitinib-treated patients that was robust and statistically significant in an analysis that was adjusted for differences in baseline IPSS risk status, which incorporates age, baseline hemoglobin, white blood cell count, constitutional symptoms, and blast count. Based on subgroup analyses, the result seems to be driven primarily by patients categorized as high risk by the IPSS scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An International Working Group project reviewing the outcome of patients with intermediate-2 or high-risk myelofibrosis over the last several decades, also found that outcome of patients had not changed over time. 23 Mindful of the caveats associated with historical comparisons, we observed an overall survival benefit for ruxolitinib-treated patients that was robust and statistically significant in an analysis that was adjusted for differences in baseline IPSS risk status, which incorporates age, baseline hemoglobin, white blood cell count, constitutional symptoms, and blast count. Based on subgroup analyses, the result seems to be driven primarily by patients categorized as high risk by the IPSS scale.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, symptom severity was decreased in the majority of patients for up to 1 year. 16,23 Serial use of the MFSAF has continued in the study, and Figure 2B illustrates that a total symptom score, defined as the composite of scores for night sweats, itching, abdominal pain and discomfort, and bone/muscle pain continues to show a median reduction of approximately 60% for more than 2 years of treatment. Four patients with symptom data did not have palpable spleen at baseline.…”
Section: Comparison To Matched Historical Controlmentioning
confidence: 99%
“…This approach has already given good results for primary myelofibrosis. 19 In the future, it will be important to investigate and dissect the precise molecular mechanisms that lead to the dramatic bone marrow alterations and that at last determine the fatal evolution of these neoplasms. This process, as a result, will allow acting even more precisely and effectively with new therapeutic tools that, from futuristic prospects, are becoming reality in many other types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…4 On a molecular level, myelofibrosis is associated with recurrent mutations of the JAK2, CALR or MPL genes. [5][6][7][8] Histologically, early myelofibrosis is characterized by increased bone marrow cellularity, with large tight clusters of atypical megakaryocytes and increased myeloid cells, with or without diffuse interstitial fibrosis. End-stage myelofibrosis also includes diffuse osteomyelosclerosis, with reduced cellularity, coarse reticulin fibers, thickened bone trabeculae and overt collagen fibrosis.…”
mentioning
confidence: 99%